A Miniature BroadBand Microstrip Antenna for LTE, Wi-Fi and WiMAX Applications - Zakaria Er-reguig; Hassan Ammor (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A Compact microstrip antenna with rectangular slotted radiating element has been developed. Four slots have been introduced on the radiating element with the use of a partial ground plane and a wideband response has been obtained. The bandwidth of the proposed antenna is 1.7 GHz with a percentage bandwidth of 71%. A low-cost dielectric (FR4_EPOXY) has been considered in the development of the proposed antenna. The obtained frequency band is from 1.9 GHz to 3.6 GHz. To investigate the robustness of our modelled antenna the simulation process has been carried out using two different solvers (Finite Element Method and Finite Integration Technique). In addition, the designed antenna was realized and these results were compared with those of the simulation. The proposed antenna is suitable for many LTE bands {1, 3, 7… 38, 40} broadly deployed in European, South American, Asian, and African countries, Wi-Fi (2.4 GHz), and WiMAX technology (3.5 GHz).